DIAGNOSTIC AND TREATMENT APPROACHES FOR ECHINOCOCCOSIS OF THE LIVER - Mishchenko, V.V.; Pustovoit, P.I.; Poliak, S.D.; Vorotyntseva, K.O.; Koychev, Ye.A.; Goryachyy, V.V.; Degtiarenko, S.P. (World of Medicine and Biology, 2022)
The purpose of the study was to improve the results of surgical treatment for echinococcosis of the liver and the quality of life of operated patients due to the improvement of diagnostic and therapeutic approaches, prevention of postoperative complications and recurrence of the disease. 22 patients were treated for echinococcosis of the liver. The duration of the operation was 2 hours in case of echinococcectomy with atypical resection of the liver, in case of laparoscopic echinococcectomy ‒ 1.2 hours, in case of puncture aspiration injection reaspiration technique ‒ 40 minutes. No fatal cases were observed. Recurrence of the disease was found in 9.1 %. A radical and effective operation is atypical resection of a part of the liver with an echinococcal cyst. Laparoscopic echinococcectomy is an alternative to open atypical resection of a part of the liver with an echinococcal cyst. The main condition for performing puncture aspiration injection reaspiration under ultrasound and X ‒ ray guidance is the absence of cystobiliary fistulae, since instillation of a cyst with a scolicidal solution can be the cause of sclerosing cholangitis. The anti-relapse antiparasitic therapy with albendazole 10‒15 mg/kg body weight twice a day or mebendazole 40‒50 mg/kg body weight three times a day in three 28-day courses with a break of 14 days should be carried out for 3‒6 months in the postoperative period.